Determinants of the Swiss Franc Real Exchange Rate - Jean-Marc Natal; Tommaso Mancini Griffoli; Christoph Meyer; Attilio Zanetti (Swiss Journal of Economics and Statistics, 2015)
We conduct an empirical investigation of the determinants of the Swiss franc real exchange rate. Theory and related empirical papers suggest various specific factors as potential determinants. We select some of these factors, and test their significance and magnitude in affecting the course of the CHF real exchange rate. Results stemming from a co-integration approach point to terms of trade and relative government spending as the most significant explanatory variables. Balassa-Samuelson effects do not play any significant role. Our results also confirm that this kind of empirical approach is sensitive to the choice of explanatory variables, panel countries and sample periods.
Keywords: C33; F31; 330; real; exchange; rate; Swiss; franc; government; consum